Soledad y ansiedad ante la muerte en adultos mayores institucionalizados y no institucionalizados, de Loja, periodo 2022 - Ortega Lozano, Jacqueline Estefanía (2022)
The aging stage is not only reduced to a biological process, but also involves a series of changes in the psychological, social, cultural and spiritual, which also demand the ability to face age-related losses, loneliness, facing one's own death and the anxiety that this may generate. The main objective of this study was to determine the relationship between loneliness and death anxiety in institutionalized and non-institutionalized elder adults. The study had a quantitative approach of non-experimental and descriptive correlational design. The population consisted of 62 older adults, residents and non-residents of geriatric institutions in Loja city. The psychological instruments used were the Social Loneliness Scale Este II and the Death Anxiety Scale DAS. For the statistical analysis of the variables, the IBM SPSS Statistics 25 software was used. The results obtained indicate that, both in the group of institutionalized and non-institutionalized older adults, a high level of loneliness predominates, while for death anxiety, both study groups presented a low level. Regarding to the statistical analysis between variables, it was found that there was no significant correlation. Finally, a psychological plan was designed for the management of loneliness and death anxiety in older adults who were part of the study, which can be applied to other geriatric institutions